Role of Personality and Emotional Intelligence in Subjective Well-Being of Medical and Engineering Students - Kaur, Manpreet (My University, 2018)
The purpose of the present study was to explore the role of personality, emotional intelligence on subjective well-being of medical and engineering students. The sample consisted of one hundred and sixty students (n=160) (80 medical and 80 engineering students) taken from two institutes of Patiala, India. The three scales were used (IPIP) by Goldberg (1992) for measuring the level of personality factors, (SSEIT) by Schutte (1998) for emotional intelligence and (PWB) given by Ryff (1989) for subjective well-being of medical and engineering students. In this study descriptive statistics, correlation and regression analysis was done. Results show that SWB is strongly associated with EI and all the personality factors. Further the results revealed that extraversion, agreeableness, conscientiousness, emotional stability and imagination and emotional intelligence were significant predictors of subjective well-being. ANOVA results showed that the interaction between gender and stream for all the variables in which engineering students are high on agreeableness, conscientiousness and medical students are high on self acceptance and among gender males are higher on subjective well-being, autonomy, positive relation and self acceptance. Therefore, stream has significant effect on SWB and also gender has significant effect on SWB.
Keywords: Personality; Emotional Intelligence; Subjective Well-Being